1981
DOI: 10.2307/1998345
|View full text |Cite
|
Sign up to set email alerts
|

Measures with Bounded Powers on Locally Compact Abelian Groups

Abstract: Abstract. If fi is a measure on a locally compact abelian group with its positive and negative convolution powers bounded in norm by K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In [4] measures with bounded powers on abelian groups were characterised by the size of the bound. In particular, it was shown that if G is a locally compact abelian group and /i is a measure on G with \\n"\\ <^(l+ > /3), for all n in Z, then fi has the form aS x for a group element x, and | a | = l. In fact, this result follows from [1, Theorem 2.6].…”
Section: Applications To Group Algebrasmentioning
confidence: 99%
“…In [4] measures with bounded powers on abelian groups were characterised by the size of the bound. In particular, it was shown that if G is a locally compact abelian group and /i is a measure on G with \\n"\\ <^(l+ > /3), for all n in Z, then fi has the form aS x for a group element x, and | a | = l. In fact, this result follows from [1, Theorem 2.6].…”
Section: Applications To Group Algebrasmentioning
confidence: 99%